Autism Paradigms, Recent Research and Clinical Applications - Fitzgerald, Michael; Yip, Jane (IntechOpen, 2017)
This book opens with a discussion of neurodiversity and an elaboration of the diagnosis of autism. It then examines factors correlating with autism, including sex bias, month of birth, migration and impact of infant feeding. The next section is on the impact of autism. The neurobiology and genetic section deals with epigenetics and intracellular pathways associated with etiology. The development and behaviour section deals with proprioceptive profiles and joint attention in autism. The final section focuses on interventions including mindfulness, animal assisted activity, social/cultural perspective on autism intervention and physical activity. The book is relevant to all professionals and researchers working with persons with autism, including psychiatrists/psychologists, speech and language therapists, occupational therapists, teachers, nurses and care workers.